1996
DOI: 10.1111/j.1600-0560.1996.tb01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudoriferous acrosyringeal acantholytic disease

Abstract: Three selected cases of transient acantholytic dermatosis were studied because of their definitive correlation with sweating due to fever and/ or bed-ridden situations. Biopsy specimens were serially sectioned and acantholysis was found in the acrosyringium or traced to connect to the acrosyringium in all biopsy specimens. Carcinoembryonic antigen (CEA) and eccrine gland-specific monoclonal antibody, IKH-4, were positive in acantholytic cells. Electron microscopy revealed electron dense material filling the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
7

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
0
14
0
7
Order By: Relevance
“…Although many have investigated the sweat gland in GD, little definite pathologic connection has been demonstrated. 30,31 We found no pathologic condition of the sweat glands in our GD patients.…”
Section: Discussionmentioning
confidence: 47%
“…Although many have investigated the sweat gland in GD, little definite pathologic connection has been demonstrated. 30,31 We found no pathologic condition of the sweat glands in our GD patients.…”
Section: Discussionmentioning
confidence: 47%
“…In 1984, Grover Regardless of the interesting work of many researchers, lack of knowledge of GD etiology persists. Initial reports suggested that poral occlusion of intraepidermal eccrine ducts might be implicated in the process, 8 but further studies have failed to confirm this possibility. 9 Despite of microscopic, immunohistochemical, 10 and ultrastructural 11 similarities of some GD lesions to Darier and Hailey-Hailey diseases, ATP2A2 gene mutations have not been found in GD.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that occlusion of eccrine duct outflow causes intraepidermal spillage of sweat contents and is responsible for the development of the disease. Hashimoto et al (11,12) described three cases of Grover's disease precipitated by heat, sweating or being bed-ridden in which the acanthoiysis appeared to be related to eccrine outflow tracts and also suggested that spillage of sweat contents may be responsible for the development of the acantholytic process in this subgroup of patients. However, histological studies and immunohistochemical studies for sweat duct specific antibodies have provided mixed results in support of this hypothesis (11)(12)(13)(14).…”
mentioning
confidence: 99%